International business & family business: Potential dialogue between disciplines - Casillas, José C.; Moreno-Menéndez, Ana M. (European Journal of Family Business, 2017)
25 years ago, Gallo and Sveen (1991) published the first paper about internationalization of family businesses. Since then, research in this area has steadily increased. In this article, I review the evolution of the literature that has combined international business and family firms (102 papers from 1991 to 2015), and I identify six promising areas for research through a dialogue between both disciplines: (1) mission and objectives of firms: the meaning of “performance”, (2) corporate government and international business, (3) attitude to risk and internationalization patterns, (4) timing, pace and speed of internationalization, (5) cross-cultural management, and (6) network perspective and social capital of firms.